The Impact of Brexit on the Swedish Economy : a Study on the Swedish Forest Products Export Sector - Lundberg, Carl (SLU/Dept. of Economics, 2018)
On the 29th of March 2019, the U.K. is scheduled to leave the European Union. This withdrawal is estimated to affect both the U.K. and economies interacting with the U.K. This thesis aims to examine whether Brexit, through its effect on the British Pound, has an impact on the Swedish export of sawn softwood. The impact of exchange rates has been tested on as well aggregate export levels as disaggregate export levels in several other studies but with mixed results. At the same time, it has not been done on the Swedish market at this disaggregated level of forestry products before and is, therefore, an interesting subject to investigate further. The data used is multivariate monthly time series data, ranging from July 2005 to September 2017. A cointegrating relationship is established by the Johansen test leading to an estimation of a Vector Error-Correction Model. Finally, the Granger Causality test tests the existence of shortrun causality amongst the variables. The results show that the exchange rate of the GBP/SEK affects the Swedish export of sawn softwood in the long term, but not in the short term. A continued stable and efficient pricing strategy could help to promote the Swedish exports of sawn softwood and retain their market power in the U.K.